Fairy of contraception: the creative process of a comic book focused on sexual education - Pinto, Mariana Silva; Silva, Maria Aparecida Alves da; Fernandes, Hylio Lagana (9 Arte (São Paulo), 2023)
It brings reflections on the creative process of a comic book about sexuality, a theme largely permeated by social factors and taboos in our current society. An analysis was made of the creative process of a comic produced as teaching material for sexual education, aimed at adolescent students in the final years of elementary and high school. The results point to the power of collective work and the importance of dialogue and openness to changes in the creation process, particularly when the theme and public objective are previously defined.